1987
DOI: 10.1002/1097-0142(19870901)60:5<1094::aid-cncr2820600529>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Esophagus and/or Gastric Cardia

Abstract: One hundred twenty-nine adenocarcinomas involving the esophagus and/or gastric cardia differed significantly from 212 cancers of the rest of the stomach as follows: male-female ratio, 6:1 versus 2:1, birth outside Canada, US or UK, 12% versus 34%; parent or sibling with gastric cancer, 5% versus 13%; previous duodenal ulcer, 23% versus 9%; chronic reflux symptoms, 25% versus 3%; hiatal hernia, 51% versus 11%. Of the 129 esophagocardia cancers, 24 involved the esophagus alone, 48 the cardia and esophagus, 33 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
44
3

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(54 citation statements)
references
References 13 publications
6
44
3
Order By: Relevance
“…Several previous reports have described a greater tendency of C-Ca than D-Ca towards deeper wall penetration, lymph node metastasis and poor prognosis, indicating that C-Ca may be a more aggressive tumour than D-Ca (Kalish et al, 1984;Wang et al, 1986;MacDonald and MacDonald, 1987;Hamilton et al, 1988;Clark et al, 1994;Ohno et al, 1995;Siewert and Stein, 1996;Kajiyama et al, 1997;Pinheiro et al, 1999;Tajima et al, 2001a). In this study, C-Ca was associated with a significantly higher prevalence of LVI than D-Ca.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Several previous reports have described a greater tendency of C-Ca than D-Ca towards deeper wall penetration, lymph node metastasis and poor prognosis, indicating that C-Ca may be a more aggressive tumour than D-Ca (Kalish et al, 1984;Wang et al, 1986;MacDonald and MacDonald, 1987;Hamilton et al, 1988;Clark et al, 1994;Ohno et al, 1995;Siewert and Stein, 1996;Kajiyama et al, 1997;Pinheiro et al, 1999;Tajima et al, 2001a). In this study, C-Ca was associated with a significantly higher prevalence of LVI than D-Ca.…”
Section: Discussionsupporting
confidence: 58%
“…It is associated with reflux symptoms, predominance in white males and a greater frequency of differentiated-type tumours as compared with adenocarcinoma of the distal stomach (D-Ca). It has also been described to show a greater tendency towards deeper wall penetration, lymph node metastasis, and a poor prognosis (Kalish et al, 1984;Wang et al, 1986;MacDonald and MacDonald, 1987;Hamilton et al, 1988;Clark et al, 1994;Ohno et al, 1995;Siewert and Stein, 1996;Kajiyama et al, 1997;Pinheiro et al, 1999;Tajima et al, 2001a). We have previously reported that early-stage of C-Ca is associated with higher frequency of gastric phenotypic marker expression and lower frequency of intestinal metaplasia of the surrounding mucosa as compared with early-stage of D-Ca (Tajima et al, 2001a).…”
mentioning
confidence: 77%
“…With regard to the sex and age of patients with EGJ adenocarcinoma in the Western world, a strong predilection exists for middle-aged and older white men [14,15]; likewise, in our Japanese series, both EGJ-and bEGJ-type patients were predominantly old men. Many of the EGJ-type carcinomas were advanced cancers, and the ratio of type-2 carcinoma was high, indicating that EGJ-type carcinomas tend to have a penetrating, expansive growth pattern, whereas bEGJ-type carcinomas tend to have a superficial spreading growth pattern.…”
Section: Discussionmentioning
confidence: 48%
“…8 High BMI is a risk factor for gastroesophageal reflux disease (GERD) and, consequently, for EAC. [9][10][11] Several studies have reported that high BMI was not associated with improved or reduced overall survival (OS) after esophagectomy, [12][13][14] although increased postoperative morbidity, such as respiratory complications, anastomotic leaks, and length of hospital stay, have been associated with high BMI in patients with gastroesophageal cancer who are undergoing surgery. 14,15 Many of these studies included small number of patients, in whom adjunctive therapy (preoperative chemotherapy and/or radiotherapy) was used.…”
mentioning
confidence: 99%